Answer:
[tex]c) \left|\begin{array}{ccc}-3&-1\\5&1\\\end{array}\right|[/tex]
Step-by-step explanation:
Given system of equations are
4 x - y = -3
-2 x +y = 5
Now the Matrix form AX = B
[tex]\left[\begin{array}{ccc}4&-1\\-2&1\\\end{array}\right][/tex][tex]\left[\begin{array}{ccc}x\\y\\\end{array}\right] = \left[\begin{array}{ccc}-3\\5\\\end{array}\right][/tex]
Now replacing first column with 'B' matrix
[tex]|A_{x} | = \left[\begin{array}{ccc}-3&-1\\5&1\\\end{array}\right][/tex]
Now replacing second column with 'B' matrix
[tex]|A_{y} | = \left[\begin{array}{ccc}4&-3\\-2&5\\\end{array}\right][/tex]